Cerebrovascular expression of proteins related to inflammation, oxidative stress and neurotoxicity is altered with aging - Tripathy, Debjani (BioMed Central, 2010)
BACKGROUND: Most neurodegenerative diseases are age-related disorders; however, how aging predisposes the brain to disease has not been adequately addressed. The objective of this study is to determine whether expression of proteins in the cerebromicrovasculature related to inflammation, oxidative stress and neurotoxicity is altered with aging. METHODS: Brain microvessels are isolated from Fischer 344 rats at 6, 12, 18 and 24 months of age. Levels of interleukin (IL)-1β and IL-6 RNA are determined by RT-PCR and release of cytokines into the media by ELISA. Vessel conditioned media are also screened by ELISA for IL-1α, monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-α, (TNFα), and interferon γ (IFNγ). Immunofluorescent analysis of brain sections for IL-1β and IL-6 is performed. RESULTS: Expression of IL-1β and IL-6, both at RNA and protein levels, significantly (p < 0.01) decreases with age. Levels of MCP-1, TNFα, IL-1α, and IFNγ are significantly (p < 0.05-0.01) lower in 24 month old rats compared to 6 month old animals. Immunofluorescent analysis of brain vessels also shows a decline in IL-1β and IL-6 in aged rats. An increase in oxidative stress, assessed by increased carbonyl formation, as well as a decrease in the antioxidant protein manganese superoxide dismutase (MnSOD) is evident in vessels of aged animals. Finally, addition of microvessel conditioned media from aged rats to neuronal cultures evokes significant (p < 0.001) neurotoxicity. CONCLUSIONS: These data demonstrate that cerebrovascular expression of proteins related to inflammation, oxidative stress and neurotoxicity is altered with aging and suggest that the microvasculature may contribute to functional changes in the aging brain.